Minat Beli Konsumen: Antara Tren, Gaya dan Kebutuhan Pada Produk Fashion - Ni Putu Ari Krismajayanti; Made Ratih Nurmalasari; Putu Putri Prawitasari; Ida Ayu Putu Megawati (Institut Daarul Qur'an Jakarta, Indonesia, 2025)
The phenomenon of fashion consumption among Generation Z reflects a shift in the functionof clothing from a basic necessity to a symbol of identity and self-expression. This study examines the consumptive behavior of Generation Z toward local fashion products, with a focus on the Gurl Bucket brand, through the lens of Maslow's hierarchy of needs. The analysis reveals that purchasing decisions are influenced not only by physiological needs but also by the need for esteem and self-actualization. Key factors such as trendy design, affordable pricing, as well as social environment and digital media influences, significantly shape consumer preferences and behaviors. These findings indicate that fashion has become an integral part of lifestyle and social representation for Generation Z. Consequently, local fashion brands are expected to continuously innovate, stay relevant to emerging trends, and foster emotional connections with consumers in order to remain competitive in a dynamic market.